Economic Feasibility Analysis Based on Optimal Cash Flow Planning on the A. Road Construction Project - Mahrusah, Safira; Putra, I Nyoman Dita Pahang (University of Merdeka Malang, 2024)
Capital resources play an important role in a project. The optimization of working capital effectively and efficiently can have a major effect on achieving the maximum profit value for the contractor. Therefore, controlling cash flow is very important. One alternative that can be used to obtain maximum profit is the right scheduling. This study aims to plan scheduling optimally using the Ms.Poject ap`plication by utilizing float time. Where the utilization of float time uses a scheme with 25% down payment and without down payment. The float time variations used are 0%, 50% and 100%. An economic feasibility analysis was conducted to review the NPV, BCR, and ROI values. From the analysis results, the greatest profitability was obtained in the alternative without a down payment using 100% float. With an NPV value of Rp16,164,849,630, BCR value of 1.0651, and ROI value of 6.51%. It can be concluded that this alternative has maximum profitability.